Conocimiento pedagógico del contenido para la enseñanza del tema mitosis: un estudio de casos con docentes universitarios de Argentina - González, Norma Viviana (2015)
The pedagogical content knowledge (PCK) for teaching mitosis at university isan unexplored field. We report the characterization of university teachers’ PCK on mitosisemploying the Content Representation questionnaire (CoRe) and Professional and Pedagogicalexperience Repertoire (PaP-eR). The differences found in the teachers’ CDC are consistent withthe characteristics of this construct: it is specific to a topic, a teacher and a context. The PCKdevelopment of university teachers in the context of teaching centered on the transmissionof knowledge emerges as a possible strategy to reorient the teaching of mitosis to approachesbased on the construction of scaffoldings that facilitate student learning.